2015
DOI: 10.1007/s11695-015-1777-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Bariatric Surgery Effective in Reducing Comorbidities and Drug Costs? A Systematic Review and Meta-Analysis

Abstract: The aim of this study was to assess drug use and costs before and after bariatric surgery (BS). A systematic review of the literature was carried out using the MeSH terms obesity, bariatric surgery, and drug costs for searches of 10 electronic databases up to July 2014. Data were extracted from the 11 studies (37,720 patients) that fulfilled the inclusion criteria. Where applicable, data were pooled by meta-analysis. The average number of drugs per patient decreased from 3.9 ± 1.86 before surgery to 1.75 ± 1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 33 publications
3
40
0
2
Order By: Relevance
“…Importantly, the features of the population and the follow-up period need to be taken into account in assessing these proportions, because the impact of surgery on antidiabetic drug use may vary according to these factors. 29 The great majority of the patients with type 2 diabetes experience more favorable results from clinical examinations, after undergoing bariatric surgery. The mortality rate associated with diabetes has also been significantly reduced.…”
Section: Antidiabetic Drugsmentioning
confidence: 99%
“…Importantly, the features of the population and the follow-up period need to be taken into account in assessing these proportions, because the impact of surgery on antidiabetic drug use may vary according to these factors. 29 The great majority of the patients with type 2 diabetes experience more favorable results from clinical examinations, after undergoing bariatric surgery. The mortality rate associated with diabetes has also been significantly reduced.…”
Section: Antidiabetic Drugsmentioning
confidence: 99%
“…Bariatric surgery is the most effective treatment for morbid obesity, resulting in a significant decrease in weight, as well as amelioration of associated co‐morbidities including type 2 diabetes mellitus (T2DM), cardiovascular diseases, obstructive sleep apnoea and musculoskeletal disorders. A decrease in the number of co‐morbidities may lead to a reduction in the healthcare resources associated with managing severe and complex obesity.…”
Section: Introductionmentioning
confidence: 99%
“…21 22 Indeed, a recent meta-analysis, comprising 37 720 patients across 11 studies, showed that bariatric surgery significantly reduces drug use and costs. 23 In addition, the direct treatment of obesity would likely help to reduce the burden on physicians who spend a substantial amount of time treating the comorbidities associated with obesity. The value of preventative strategies for obesity is an important consideration for decision makers, particularly given the increasing concern over the sustainability of the healthcare system and the ageing population.…”
Section: Discussionmentioning
confidence: 99%